(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
Electrochemical behaviour of catechol, hydroquinone and resorcinol was investigated in KCl, acetate buffer and phosphate buffer at glassy carbon electrod using cyclic voltammetry. The results imply that the glassy carbon electrode exhibited a synergistic and excellent electrocatalytic effect on the redox behaviors of the benzenediols. Catechol and hydroquinone show one pair of redox peaks in acetate and phosphate buffer but two pairs of redox peaks in KCl. In all cases the redox process is quasireversible. Resorcinol behaves almost irreversibly in all three electrolytic media. Good linear relationships were obtained between the peak currents and the concentrations of benzenediols. The electrochemical process in all the isomers was controlled by diffusion process. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 135-146, 2015